KPIs for Sustainability: Defining the Strategy for a Sustainable Future in the Insurance Industry (Junior Management Science, 2025)
Sustainability transformation has gained traction across industries worldwide. Given their critical risk exposure, this transformation is of extreme precarity to the insurance industry. Yet, literature lacks a comprehensive approach for the development of a sustainability strategy covering the environmental, social and governance (ESG) dimensions. This work bridges the gap by evaluating methods for defining sustainability Key Performance Indicators (KPIs) and their integration into strategy. A roadmap is then developed that guides successful strategy implementation. Based on a systematic literature review of 5.000+ academic papers, this work features a quantitative and qualitative analysis of literature and evaluates four core papers on the definition of sustainability KPIs for the insurance industry. Leadership commitment and ESG integration into core business emerge as the most important factors towards a successful transformation. The resulting sustainability roadmap provides a blueprint for insurers to embed ESG values, enabling businesses of all sizes to participate. This work contributes to academia and industry by supporting the development of comprehensive and successfully integrated sustainability strategies.Keywords: insurance; KPIs; strategy; sustainability; transformation